Clinical predictors of all‐cause mortality in patients presenting to specialist heart failure clinic with raised NT‐proBNP and no heart failure. (4th June 2020) - Garg, Pankaj; Wood, Steven; Swift, Andrew J.; Fent, Graham; Lewis, Nigel; Rogers, Dominic; Rothman, Alexander; Charalampopoulos, Athanasios; Al‐Mohammad, Abdallah
Abstract: Aims: Clinical outcomes for patients suspected of having heart failure (HF) who do not meet the diagnostic criteria of any type of HF by echocardiography remain unknown. The aim of this study was to investigate the clinical predictors of all‐cause mortality in patients with suspected HF, a raised N‐terminal pro‐b‐type natriuretic peptide (NTproBNP) and who do not meet the diagnostic criteria of any type of HF by echocardiography. Methods and results: Relevant data were taken from the S heffield HEA rt F ailure (SHEAF) registry (222349P4). The inclusion criteria were presence of symptoms raising suspicion of HF, NTproBNP > 400 pg/mL, and preserved left ventricular function. Exclusion criteria were any type of HF by echocardiography. The outcome was defined as all‐cause mortality. Cox proportional‐hazards regression model was used to investigate the association between the survival time of patients and clinical variables; 1031 patients were identified with NTproBNP > 400 pg/mL but who did not have echocardiographic evidence of HF. All‐cause mortality was 21.5% (222 deaths) over the mean follow‐up (FU) period of 6 ± 2 years. NTproBNP was similar in patients who were alive or dead ( P = 0.96). However, age (HR 1, P < 0.01), chronic kidney disease (CKD, HR 1.2, P < 0.01), chronic pulmonary obstructive disease (COPD, HR 1.6, P < 0.01), dementia (HR 5.9, P < 0.01), male gender (HR 1.4, P < 0.01), first‐degree atrioventricular block (HR 2.1, P < 0.01), left axis deviation (HR 1.6, P = 0.04), and diabetes (HR 1.4, P = 0.03) were associated with all‐cause mortality. In multivariate regression, age, gender, CKD stage, COPD, and dementia were independently associated with mortality. In patients with NTproBNP > 627 pg/mL, NYHA class predicted death (II, 19.6%; III, 27.4%; IV, 66.7%; P < 0.01). Conclusions: Patients with no HF on echocardiography but raised NTproBNP suffer excess mortality particularly in the presence of certain clinical variables. Age, male gender, worsening CKD stage, presence of COPD, and dementia are independently associated with all‐cause mortality in these patients. An NTproBNP > 627 pg/mL coupled with NYHA class could identify patients at greatest risk of death.